International validation of harmonized definitions for complications of blood donations. Issue 11 (8th October 2018) - Land, Kevin J.; Townsend, Mary; Goldman, Mindy; Whitaker, Barbee I.; Perez, Gabriela E.; Wiersum‐Osselton, Jo C.
Abstract : BACKGROUND: In December 2014, a multinational collaboration of hemovigilance experts from the International Society of Blood Transfusion (ISBT), the International Hemovigilance Network, and AABB published harmonized definitions of complications related to blood donation titled "Standard for Surveillance of Complications Related to Blood Donation." Both mandatory and optional terms were included. The definitions are endorsed by the Alliance of Blood Operators and the European Blood Alliance. STUDY DESIGN AND METHODS: The objective of this study was to validate harmonized donor hemovigilance definitions with potential users. In June 2016, 30 real‐world cases were sent to potential users around the world along with the definitions, an answer sheet, and instructions on how to complete the validation exercise. RESULTS: Overall, 54 responses from 25 countries were received, including over 400 comments. The results were presented for feedback at both ISBT and AABB meetings. Case diagnoses were consistent across most responders. Exceptions were rare adverse events, nonstandard presentations, or incomplete information. In general, the application of optional definitions, including severity grading and imputability, had the most variability. CONCLUSION: The use of standardized terms in the donor setting serves to increase focus on donor safety, facilitate conversation, foster exchange of information, and frame questions for future research. Overall, the definitions provide adequate coverage of donor reactions; however, some terms require clarification. Severity grading and imputability and other optional terms need clear and objective definitions and instructions on when and how to use them. Additional feedback and final recommendations are summarized in this report.